Analysis of Service Quality of Teacher Training Program at Semarang Training Center, Ministry of Religious Affairs Servqual and ZOT of Teacher Training Programs - Lily Nurulia; Masrukhi Masrukhi; Tri Joko Raharjo; Edy Purwanto (Universitas Negeri Semarang, 2021)
Training participants’ satisfaction can be achieved by providing good quality service. Therefore, Semarang Training Centre of Ministry of Religious Affairs (MORA) as a training service provider must focus on the satisfaction of training participants as consumers. Good service performance and the fulfillment of training participants' expectations will greatly affect the satisfaction of the users. This study aims to identify differences between the reality and expectations of the training participants for the services of the training providers and to analyze the quality of training services provided by training providers with service quality and zone of tolerance methods. Based on the value in servqual method, it was found that the quality of the training committee's service providers has satisfied the training participants as customers in high score. Whereas the value with the ZoT method found that out of the 15 services attributes of the training committee, there were 13 service attributes that had been tolerated by the training participants. The other two attributes cannot be tolerated by training participants as customers and must be repaired immediately.